Extreme site fidelity in long‐distance migratory shorebirds in Australia and potential implications for conservation - Tobias A. Ross; Robyn Atkinson; Maureen Christie; Danny I. Rogers; Chris Hassell; Roz Jessop; Jonathan T. Coleman; Theunis Piersma; Sara Ryding; Aaron Spence; Marcel Klaassen (Conservation Biology, 2026)
Site fidelity is the tendency for animals to repeatedly return to the same locations, either within or between years. Site fidelity enables animals to utilize knowledge of previously visited locations, including assessments of seasonal variations in health and mortality risks (e.g., predation), resource availability, and social benefits such as pairing with previous mates. However, rigidly enacted site fidelity may come with fitness costs in times of rapid habitat change. One group believed to exhibit site fidelity is migratory shorebirds (families Charadriidae and Scolopacidae). Shorebirds that migrate annually via the East Asian–Australasian Flyway have experienced rapid population declines due to habitat loss in Asia. Although high site fidelity may influence these declines under a global change scenario, only limited, species‐specific analyses of site fidelity have been previously conducted. Our study used an extensive dataset of 636,167 records of over 84,000 banded individual shorebirds from 1976 to 2025 to present an overview of site fidelity for 12 migratory shorebird species during their nonbreeding season in Australia. We found overall site fidelity of >95% across 10 out of 12 species, with the only exceptions being red knot ( Calidris canutus ) and sanderling ( Calidris alba ), with movements often limited to sections of coastline less than 20 km long. Juvenile and immature birds were usually less site faithful than adults. The high site fidelities of most species suggest that local site knowledge is of considerable importance and that individuals forced to relocate to alternative sites will likely incur a cost. Our findings also imply that habitat loss may have immediate population‐level consequences through reduced fitness of displaced birds.

Diarrhoea in children under 5 years in two informal settlements in Accra, Ghana: The impact of antecedent rainfall and flooding - Mehmet A. Veral; Manoj Roy; Roger W. Pickup; Richard Bayitse; Pat M. Agbedor; Mark Akrong; Peter M. Atkinson (Environmental Research, 2026)

Correction to: Biomarkers of cellular senescence and major health outcomes in older adults - Steven R. Cummings; Li‑Yung Lui; Zaira Aversa; Theresa Mau; Roger A. Fielding; Elizabeth J. Atkinson; Sheena Patel; Nathan LeBrasseur (GeroScience, 2025)

Biomarkers of cellular senescence and major health outcomes in older adults - Steven R. Cummings; Li-Yung Lui; Aversa Zaira; Theresa Mau; Roger A. Fielding; Elizabeth J. Atkinson; Sheena Patel; Nathan LeBrasseur (GeroScience, 2024)
The geroscience hypothesis proposes that underlying biological processes, such as the accumulation of senescent cells, have deleterious effects on multiple tissues and increase the risk of many chronic conditions with aging. Senescent cells produce heterogenous biomarkers, also called senescence-associated secretory phenotype (SASP). Circulating concentrations of senescence biomarkers may reflect an underlying burden of senescent cells in various tissues. Plasma levels of these proteins have been associated with increased mortality and poorer physical function. The associations of them with the incidence of major age-related conditions including heart failure, cardiovascular disease, stroke, and dementia, have not been studied. We measured 35 senescence biomarkers in baseline plasma samples from 1678 participants aged 70–79 years old in the longitudinal Health ABC cohort study. Clinical outcomes were ascertained and validated over an average 11.5 year follow-up. In models adjusted for age, sex, and race, higher levels of most of senescence biomarkers were associated with increased risk of all-cause mortality, mobility limitation, and heart failure. Several were also associated with an increased risk of coronary heart disease, stroke, and dementia. Very few were associated with the risk of cancer. Proteins that were selected by Lasso regression for each outcome that commonly included GDF15 and IL6, significantly improved the prediction of mortality, mobility limitation, and heart failure compared with age, sex, and race alone. These results indicate that levels of senescence biomarkers predict an increased risk of several age-related clinical outcomes and may identify individuals most likely to benefit from senotherapeutics.

Associations between biomarkers of cellular senescence and physical function in humans: observations from the lifestyle interventions for elders (LIFE) study - Roger A. Fielding; Elizabeth J. Atkinson; Zaira Aversa; Thomas A. White; Amanda A. Heeren; Sara J. Achenbach; Michelle M. Mielke; Steven R. Cummings; Marco Pahor; Christiaan Leeuwenburgh; Nathan K. LeBrasseur (GeroScience, 2022)
Cellular senescence is a plausible mediator of age-associated declines in physical performance. To test this premise, we examined cross-sectional associations between circulating components of the senescence-associated secretory phenotype (SASP) and measures of physical function and muscle strength in 1377 older adults. We showed significant associations between multiple SASP proteins and the short physical performance battery (SPPB), its subcomponents (gait speed, balance, chair rise time), and 400-m walk time. Activin A, ICAM1, MMP7, VEGFA, and eotaxin showed strong associations based on gradient boost machine learning (GBM), and, when combined with other proteins, effectively identified participants at the greatest risk for mobility disability (SPPB score $$\le$$ ≤ 7). Senescence biomarkers were also associated with lower grip strength, and GBM identified PARC, ADAMTS13, and RANTES as top candidates in females, and MMP2, SOST, and MCP1 in males. These findings highlight an association between senescence biomarkers and physical performance in older adults. ClinicalTrials.gov Identifier: NCT01072500.

Information infrastructure for Australia’s Integrated Marine Observing System - Marton G. Hidas; Roger Proctor; Natalia Atkins; Julian Atkinson; Laurent Besnard; Peter Blain; Philip Bohm; Jon Burgess; Kim Finney; Dan Fruehauf; Guillaume Galibert; Xavier Hoenner; et al. (Earth Science Informatics, 2016)

What is the impact of systematically missing exposure data on air pollution health effect estimates? - Evangelia Samoli; Roger D. Peng; Tim Ramsay; Giota Touloumi; Francesca Dominici; Richard W. Atkinson; Antonella Zanobetti; Alain Le Tertre; H. Ross Anderson; Joel Schwartz; Aaron Cohen; Daniel Krewski; et al. (Air Quality, Atmosphere & Health, 2014)

Acute effects of ambient ozone on mortality in Europe and North America: results from the APHENA study - Roger D. Peng; Evangelia Samoli; Luu Pham; Francesca Dominici; Giota Touloumi; Tim Ramsay; Richard T. Burnett; Daniel Krewski; Alain Le Tertre; Aaron Cohen; Richard W. Atkinson; H. Ross Anderson; et al. (Air Quality, Atmosphere & Health, 2013)

Coral disease following massive bleaching in 2005 causes 60% decline in coral cover on reefs in the US Virgin Islands - J. Miller; E. Muller; C. Rogers; R. Waara; A. Atkinson; K. R. T. Whelan; M. Patterson; B. Witcher (Coral Reefs, 2009)

Kinetics of the Gas-Phase Reactions of OH Radicals, NO3 Radicals and O3 with Three C7-Carbonyls Formed From The Atmospheric Reactions of Myrcene, Ocimene and Terpinolene - Jillian Baker; Janet Arey; Roger Atkinson (Journal of Atmospheric Chemistry, 2004)

A media-based assessment of damage and ground motions from the january 26th, 2001M 7.6 Bhuj, India earthquake - Susan E Hough; Stacey Martin; Roger Bilham; Gail M Atkinson (Journal of Earth System Science, 2003)

Kinetics and Products of the Gas-Phase Reaction of OH Radicals with 5-Hydroxy-2-Pentanone at 296± 2 K - Sara M. Aschmann; Janet Arey; Roger Atkinson (Journal of Atmospheric Chemistry, 2003)

Transformations of Pesticides in the Atmosphere: A State of the Art - Roger Atkinson; Rob Guicherit; Ronald A. Hites; Wolf-Ulrich Palm; James N. Seiber; Pim de Voogt (Water, Air, & Soil Pollution, 1999)

Kinetics of the Gas-Phase Reactions of OH and NO3 Radicals and O3 with the Monoterpene Reaction Products Pinonaldehyde, Caronaldehyde, and Sabinaketone - Alvaro Alvarado; Janet Arey; Roger Atkinson (Journal of Atmospheric Chemistry, 1998)

Radiometric dating of the Middle Palaeolithic tool industry and associated fauna of Pin Hole Cave, Creswell Crags, England - Roger M. Jacobi; Peter J. Rowe; Mabs A. Gilmour; Rainer Grün; Timothy C. Atkinson (Journal of Quaternary Science, 1998)

Radiometric dating of the Middle Palaeolithic tool industry and associated fauna of Pin Hole Cave, Creswell Crags, England - Roger M. Jacobi; Peter J. Rowe; Mabs A. Gilmour; Rainer Grün; Timothy C. Atkinson (Journal of Quaternary Science, 1998)

Kinetics of the atmospherically important gas-phase reactions of a series of trimethyl phosphorothioates - Mark A. Goodman; Sara M. Aschmann; Roger Atkinson; Arthur M. Winer (Archives of Environmental Contamination and Toxicology, 1988)

Atmospheric gas phase loss processes for chlorobenzene, benzotrifluoride, and 4-chlorobenzotrifluoride, and generalization of predictive techniques for atmospheric lifetimes of aromatic compounds - Roger Atkinson; Sara M. Aschmann; Arthur M. Winer; James N. Pitts (Archives of Environmental Contamination and Toxicology, 1985)

A study of the atmospheric reactions of 1,3-dichloropropene and other selected organochlorine compounds - Ernesto C. Tuazon; Roger Atkinson; Arthur M. Winer; James N. Pitts (Archives of Environmental Contamination and Toxicology, 1984)